1996
DOI: 10.1152/ajpendo.1996.270.2.e265
|View full text |Cite
|
Sign up to set email alerts
|

Progressive effect of endurance training on metabolic adaptations in working skeletal muscle

Abstract: We investigated the hypothesis that a program of prolonged endurance training, previously shown to decrease metabolic perturbations to acute exercise within 5 days of training, would result in greater metabolic adaptations after a longer training duration. Seven healthy male volunteers [O2 consumption = 3.52 +/- 0.20 (SE) l/min] engaged in a training program consisting of 2 h of cycle exercise at 59% of pretraining peak O2 consumption (VO2peak) 5-6 times/wk. Responses to a 90-min submaximal exercise challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
155
5
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(184 citation statements)
references
References 16 publications
21
155
5
3
Order By: Relevance
“…Given the acute reductions observed for some enzymes, such as COX and hexokinase during exercise, it is clear that the reductions are transitory, recovering between exercise days (hexokinase) or by the 2nd day of inactivity. The failure to find increases in the maximal activities of the CAC and the rate-limiting enzymes of glycogenolysis and glycolysis during the recovery days was not surprising, given the results of several previous experiments that have reported no change in response to several sessions of exercise (21,61). To our knowledge, decreases in COX have not been reported with either exercise or short-term training.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Given the acute reductions observed for some enzymes, such as COX and hexokinase during exercise, it is clear that the reductions are transitory, recovering between exercise days (hexokinase) or by the 2nd day of inactivity. The failure to find increases in the maximal activities of the CAC and the rate-limiting enzymes of glycogenolysis and glycolysis during the recovery days was not surprising, given the results of several previous experiments that have reported no change in response to several sessions of exercise (21,61). To our knowledge, decreases in COX have not been reported with either exercise or short-term training.…”
Section: Discussionmentioning
confidence: 70%
“…These studies indicate that training-like adaptations can be observed within the first few sessions of regular exercise in the absence of increases in V max of a range of mitochondrial enzymes (21,28,61). Current evidence indicates that the metabolic adaptations are mediated by events outside of the muscle, namely, increased V O 2 kinetics during the nonsteady rate (60), which occurs secondary to a more rapid adjustment in blood flow (71).…”
mentioning
confidence: 99%
“…The effects of exercise training on TG m content in healthy subjects are equivocal, with some studies reporting an increase [11,24,25], decrease [26] or no [9,10,27] after short-term (6-12 weeks) endurance exercise. In our investigation, exercise training had little effect on TG m concentrations in control subjects, but resulted in a substantial overall decrease in patients with Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that endurance training elicits an increase in the oxidative capacity of skeletal muscle from healthy, insulin-sensitive subjects [25,36,37]. Thus, regular exercise training might be therapeutic in overcoming derangements in lipid metabolism observed in Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, a entrada de AG no plasma é similar à taxa de oxidação no mesmo período. Alguns pesquisadores sugerem que outra fonte de lipídios, além dos AG provenientes do tecido adiposo, provavelmente plasmático ou TGIM, é também oxidada pelo músculo (18,19).…”
Section: Metabolismo Dos Triacilgliceróis Intramusculares (Tgim)unclassified